Modus Tindak Pidana Pencucian Uang di Perdagangan Pasar Modal - Jamilah Aqthar; M. Faisal Husna; Maunalisa Maunalisa; Muhammad Zainuddin; Fika Azhari Nasution (Jurnal Syntax Admiration, 2024)
This study aims to identify and analyze the modus operandi used in money laundering in the capital market trading sector. The research method used is a normative education method that looks at matters related to law, both formal and non-formal law and analyzes primary data and secondary data. The results of money laundering research in the capital market can occur by the placement, layering, and integration process through the capital market. As a result, money laundering in the capital market is growing rapidly, especially with the use of the capital market as a means of laundering money proceeds of crimes such as corruption. Securities buying and selling activities in the capital market are difficult to supervise because of their complexity and actors can practice market manipulation with the Placement, Layering, and Integration methods. Although regulations related to money laundering in the capital market are not yet firm, supervisory and law enforcement agencies have their own regulations. To minimize this crime, good cooperation between authorized institutions is needed.